SOSIALISASI PERMAINAN TRADISIONAL PALEMBANG SEBAGAI UPAYA PELESTARIAN BUDAYA DI TK NEGERI PEMBINA 2 PALEMBANG - Santa Idayana sinaga; Padilah padilah; Rahmah Novianti; Melinda Puspita Sari Jaya; Fatma Rizki Intan; Mardiana Mardiana; Tuti Firdayani; Dessi Andriani (Kreasi: Jurnal Pengabdian Masyarakat, 2026)
This Community Service (PKM) activity was carried out as an effort to increase the understanding of PAUD teachers regarding the importance of preserving local culture through traditional Palembang games. Partners' problems included teachers' low understanding in integrating traditional games into learning and children's declining interest in local culture. This activity aims to improve teachers' skills in implementing traditional games as a medium for early childhood learning. The implementation method was carried out through the stages of needs observation, material socialization, traditional game implementation practice, mentoring, and activity evaluation. 15 participants consisting of teachers and the principal of Pembina 2 Palembang State Kindergarten. The results of the activity showed an increase in teachers' understanding of local culture preservation and teachers' ability to design traditional game-based learning activities. In addition, participants showed high enthusiasm throughout the activity. The activity contributed positively to quality of PAUD learning which is more contextual, enjoyable, and based on local culture.